A Controlled Study of a Group Mindfulness Intervention for Individuals Living With Inflammatory Bowel Disease. Issue 3 (March 2016) - Neilson, Kate; Ftanou, Maria; Monshat, Kaveh; Salzberg, Mike; Bell, Sally; Kamm, Michael A.; Connell, William; Knowles, Simon R.; Sevar, Katherine; Mancuso, Sam G.; Castle, David
Abstract : Background: This study aimed to evaluate the feasibility, acceptability, and effectiveness of a mindfulness-based intervention for patients with inflammatory bowel disease (MI-IBD). Design: Treatment-as-usual control versus mindfulness-based stress reduction intervention. Methods: Sixty patients participated in either the MI-IBD (n = 33) or treatment-as-usual group (n = 27) conditions. The MI-IBD consisted of an 8-week mindfulness-based stress reduction training group. Outcome measures were administered at baseline (before intervention), immediately after intervention, and 6 months after intervention. Primary outcomes included measures of quality of life, psychological distress (depression and anxiety), and mindfulness. Data for MI-IBD group participants also included weekly attendance, daily minutes meditated, and satisfaction with the program. Results: There were no baseline differences between intervention and control groups on demographic variables or inflammatory bowel disease severity. Compared with the control group, the MI-IBD group reported significantly greater improvements in anxiety, quality of life, and mindfulness at after intervention, with reduction in depression and improvements in quality of life and mindfulness maintained at 6 months after intervention. Conclusions: Results demonstrate the feasibility, acceptability, and efficacy of a mindfulness intervention for patients with inflammatory bowel disease, with medium-to-large effects on psychological distress, quality of life, and mindfulness. Abstract : Article first published online 4 November 2015.